Overview of Prescription Administration Screening for Antihypertensive Drugs at Pharmacy X in Bengkulu City - Lestari, Gina; Dharmayanti, Luky (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Prescription screening is an activity carried out by pharmacists in reviewing the completeness of prescriptions administratively, pharmaceutically and clinically before the drug is prepared. This activity is carried out to avoid medication errors in patients which can result in the patient not achieving drug therapy. The aim of this study was to determine the administration screening of antihypertensive prescriptions at one of the pharmacies in the city of Bengkulu. This research is descriptive observational in nature and data collection and retrieval was carried out using a retrospective method where data was taken on prescriptions in 2023. The number of antihypertensive prescriptions obtained was 97 pieces. The research results were obtained from patient data, namely (name 100%, age 35%, gender 71%, weight 0%, and address 1%) with an average of 41.4%. Meanwhile, the doctor's data information is (name 84%, SIP number 59%, address 81%, telephone number 22%, initials 43%, and date of prescription writing 82%) with an average of 57.8%. It can be concluded that the screening of antihypertensive prescription administration at one of the pharmacies in Bengkulu City is not complete.Â